Physical properties of the magnetically frustrated very-heavy-fermion compound YbCu4Ni - Sereni, J.G.; Čurlík, I.; Giovannini, M.; Strydom, A.; Reiffers, M.; Sereni, Julián (American Physical Society, 2018)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina